Clinical aspects of infertile 47, XYY patients: a retrospective study. (3rd April 2019) - Borjian Boroujeni, Parnaz; Sabbaghian, Marjan; Vosough Dizaji, Ahmad; Zarei Moradi, Shabnam; Almadani, Navid; Mohammadpour Lashkari, Faranak; Zamanian, Mohamad Reza; Mohseni Meybodi, Anahita
Abstract: 47, XYY syndrome is a sex chromosomal anomaly in men, which may be associated with infertility and has an incidence of 0.1% of male births. The clinical and paraclinical characteristics of men suffering from this anomaly have not been fully described. In this retrospective study, we present 37 cases of 47, XYY infertile men with sperm counts varying from normal to azoospermia, referred to the Genetics Laboratory at the Royan Institute, Iran. Thirteen individuals were mosaic and 24 non-mosaics. Non-mosaic patients were classified as azoospermic (nine cases) and normospermic/oligozoospermic men (15 cases). Two of the non-mosaic and three mosaic patients had secondary infertility. In addition, 13 of them underwent IUI, IVF or ICSI, and in seven cases, there was a biochemical pregnancy. The remaining 14 patients did not have ART. The 47, XYY syndrome is relatively unusual and can be missed clinically because of the lack of symptoms and of diverse phenotypes. Diagnosis of this aneuploidy can provide valuable data for counselling and early management of the patients who undergo fertility evaluation.